Instrumental balance assessment in Parkinson's disease and parkinsonism. A systematic review with critical appraisal of clinical applications and quality of reporting - Andrea Merlo; Lorenzo Cavazzuti; Maria Chiara Bò; Francesco Cavallieri; Maria Chiara Bassi; Benedetta Damiano; Sara Scaltriti; Valentina Fioravanti; Giulia Di Rauso; Giulia Di Rauso; Giacomo Portaro; Franco Valzania; et al. (Frontiers in Neurology)
IntroductionPatients with Parkinson's disease (pwPD) and atypical parkinsonism usually complain of impaired balance. Instrumental posturography is widely used to quantitatively assess static balance in pwPD but many posturographic parameters and protocols have been suggested. We aimed to appraise the use of static posturography in pwPD and atypical parkinsonism, and identify gaps hindering its translation into clinical routine.MethodsA systematic review on four databases. Study methodology, clinical aspects, assessment protocol, technical aspects, and transferability to clinical practice were critically appraised by a set of quality questions, scored on three levels (0, 0.5, 1). Total scores were used to assess overall studies' quality.Results132 studies were included. The majority (105/132) was rated medium-quality. The domains “transferability to clinical practice” and “assessment protocol” received the lowest scores. The main flaw hindering portability to clinical settings was the lack of a stated rationale behind the choice of a specific protocol and the selection of the posturographic parameters. Missing reporting about the technical aspects employed to manage posturographic data and comprehensive instructions given to the patients further contributed to lower quality.DiscussionWe provided recommendations for enhancing the clinical transferability of studies on static posturography to assess pwPD, including (1) discussing the rationale for choosing the assessment protocols and posturographic parameters, (2) detailing the inclusion criteria and select appropriate samples, and (3) reporting all the technical information to replicate the procedures and computations.Systematic review registrationInternational Prospective Register of Systematic Reviews (PROSPERO) on 6th February 2024 (ID CRD42024500777), https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024500777.